Preparation method of high-capacity hard carbon negative electrode material for sodium ion battery

CN117374276BActive Publication Date: 2026-11-03CHENGDU EMINENT NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311401302.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2026-11-03
Estimated Expiration
2043-10-26

AI Technical Summary

Technical Problem

现有硬碳材料结构不易调控,导致钠离子吸附能力弱,造成可逆容量低,且现有改善方法工艺复杂难以控制。

Method used

Using biochar as raw material, the process involves crushing, acid washing, and drying, followed by pretreatment under a protective atmosphere. Then, a step-by-step carbonization process, including low-temperature and high-temperature carbonization, is used to adjust the micropore volume ratio, reduce the specific surface area, and improve the initial efficiency.

Benefits of technology

High-capacity, high-efficiency hard carbon anode materials were prepared, with easily controllable pore structure, making them suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117374276B_ABST
    Figure CN117374276B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of negative material preparation, in particular to a preparation method of high-capacity hard carbon negative material for sodium ion batteries. The method comprises the following steps: A, biomass carbon is crushed, pickled, washed, filtered and dried to obtain a first hard carbon precursor; the biomass carbon can be solid carbon material prepared by high-temperature pyrolysis or oxidation treatment of coconut shell, starch, straw, bamboo and the like; B, the first hard carbon precursor obtained in the step A is pretreated under atmosphere protection to remove redundant water, and pretreated material is obtained; C, the pretreated material obtained in the step B is coated by a coating agent to obtain a second hard carbon precursor, and carbonization is carried out under atmosphere protection to obtain the hard carbon negative material. The hard carbon negative material prepared by the application improves reversible capacity, controls carbonization temperature and reduces specific surface area, so that the initial efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of anode material preparation technology, and in particular to a method for preparing a high-capacity hard carbon anode material for sodium-ion batteries. Background Technology

[0002] Hard carbon materials are mainly made from biochar such as coconut shells, starch, straw, and bamboo. These biochars typically have well-developed pores, are widely available, and are inexpensive. However, their structure is difficult to control, and their surface has significant defects. Their structure is mainly composed of mesopores and macropores, resulting in weak sodium ion adsorption capacity and low reversible capacity. Currently, the industry mainly improves the interlayer spacing of hard carbon and enhances sodium ion kinetics through doping, but this method has low initial efficiency. Another approach involves selecting porous carbon as a precursor and acetylene or other materials as pyrolysis carbon sources. The pore size of the porous carbon surface is adjusted through chemical vapor deposition, followed by high-temperature carbonization to form graphite-like microcrystals inside the porous carbon. However, this process is complex, making it difficult to control the internal micropore structure. Insufficient deposition cannot reduce the specific surface area to improve initial efficiency, while excessive deposition reduces the micropore volume, thus decreasing the sodium ion storage space. Summary of the Invention

[0003] To address the aforementioned technical problems, the present invention aims to provide a method for preparing a high-capacity hard carbon anode material for sodium-ion batteries.

[0004] To achieve the above objectives, the embodiments of the present invention adopt the following technical solutions:

[0005] This invention provides a method for preparing a high-capacity hard carbon anode material for sodium-ion batteries, comprising the following steps:

[0006] A. The first hard carbon precursor is obtained by crushing, acid washing, washing, filtering and drying the biochar. The biochar can be a solid carbon material made from raw materials such as coconut shell, starch, straw, and bamboo through high-temperature pyrolysis or oxidation treatment.

[0007] B. Under a protective atmosphere, the first hard carbon precursor obtained in step A is pretreated to remove excess moisture and obtain pretreated material.

[0008] C. The pretreated material obtained in step B is coated with a coating agent to obtain a second hard carbon precursor, and then carbonized under a protective atmosphere to obtain a hard carbon anode material.

[0009] In some embodiments, in step A, the average pore size of the first hard carbon precursor is 25-40 nm, wherein the total pore volume ratio of mesopores and macropores is 90-100%, the pore volume ratio of micropores is 0-10%, and the specific surface area is 100-500 m². 2 / g, with a particle size of 1-20μm.

[0010] In some embodiments, in step A, the pulverization is air jet milling, mechanical milling, or roller milling.

[0011] In some embodiments, during step A, the pulverized biochar, water, hydrochloric acid, nitric acid and hydrofluoric acid are mixed in a mass ratio of 1:(1-10):(0.1-10):(0-15):(0-5) during the pickling process.

[0012] In some embodiments, in step B, the pretreatment temperature is 200-500℃, the heating rate is 0.5-5℃ / min, and the holding time is 1-5h.

[0013] In some embodiments, in step C, the coating agent includes at least one of coal tar pitch, petroleum pitch, natural pitch, phenolic resin and epoxy resin, and the mass ratio of the coating agent to the first hard carbon precursor is (1-10):100.

[0014] In some embodiments, in step C, the carbonization includes the following steps: first, pre-carbonizing at a temperature of 500-1000℃ with a heating rate of 0.5-5℃ / min and a holding time of 1-5h; and then carbonizing again at a temperature of 1000-1600℃ with a heating rate of 0.5-5℃ / min and a holding time of 1-5h.

[0015] In some embodiments, in step C, the hard carbon anode material has an average pore size of 1-10 nm, a total pore volume ratio of 0-20% for mesopores and macropores, a pore volume ratio of 80-100% for micropores, and a specific surface area of ​​1-5 m². 2 / g, with a particle size of 1-10μm.

[0016] The hard carbon anode material prepared by this invention uses well-porous biochar as raw material and processes it by crushing, acid washing, and drying to obtain a hard carbon precursor, which is then obtained by stepwise carbonization. The hard carbon anode material prepared by this method has the characteristics of high capacity, high initial efficiency, and stable performance. The pore structure of this material is mainly adjusted by controlling the carbonization temperature to regulate the proportion of micropore volume, thereby increasing the sodium ion storage space and improving the reversible capacity. Controlling the carbonization temperature reduces the specific surface area, thereby improving the initial efficiency. The preparation process is simple and the process conditions are easy to adjust and control, which can be better applied to industrial production. Attached Figure Description

[0017] Figure 1 TEM image of the hard carbon anode material prepared in Example 2;

[0018] Figure 2 The charge-discharge curve of the hard carbon anode material prepared in Example 2 is shown below.

[0019] Figure 3 The image shows the pore size distribution of the hard carbon anode material prepared in Example 2. Detailed Implementation

[0020] The technical solutions in some embodiments of this disclosure will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this disclosure, and not all embodiments. Based on the embodiments provided in this disclosure, all other embodiments obtained by those skilled in the art are within the scope of protection of this disclosure.

[0021] Example 1

[0022] A. Using coconut shell carbon grown in Indonesia as raw material, the coconut shell carbon is pulverized to a median particle size of 10±0.5μm using an air jet mill. The pulverized material, water, hydrochloric acid, nitric acid and hydrofluoric acid are mixed in a ratio of 1:1.5:0.1:1.5:0.1 and stirred in a reaction vessel for 8 hours. After washing with deionized water until pH=6, the mixture is dried.

[0023] B. Transfer the obtained material to a carbonization furnace and heat it to 300°C at a rate of 5°C / min under nitrogen atmosphere protection. Hold the temperature for 3 hours to perform low-temperature pretreatment to remove excess moisture and volatiles, and obtain the material to be pretreated.

[0024] C. After the pretreated material cools down naturally, it is taken out and coated with phenolic resin in liquid phase. The mass ratio of phenolic resin to pretreated material is 8:100. After uniform dispersion, it is heated to 500℃ at a rate of 3℃ / min under nitrogen atmosphere protection and carbonized for 3 hours. After the carbonized material cools down naturally, it is heated to 1300℃ at a rate of 3℃ / min under nitrogen atmosphere protection and carbonized for 3 hours to obtain hard carbon anode material.

[0025] Example 2

[0026] A. Using coconut shell carbon grown in Indonesia as raw material, the coconut shell carbon is pulverized to a median particle size of 10±0.5μm using an air jet mill. The pulverized material, water, hydrochloric acid, nitric acid and hydrofluoric acid are mixed in a ratio of 1:1.5:0.1:1.5:0.1 and stirred in a reaction vessel for 8 hours. After washing with deionized water until pH=6, the mixture is dried.

[0027] B. Transfer the obtained material to a carbonization furnace and heat it to 300°C at a rate of 5°C / min under nitrogen atmosphere protection. Hold the temperature for 3 hours to perform low-temperature pretreatment to remove excess moisture and volatiles, and obtain the material to be pretreated.

[0028] C. After the pretreated material cools down naturally, it is taken out and coated with phenolic resin in liquid phase. The mass ratio of phenolic resin to pretreated material is 8:100. After uniform dispersion, it is heated to 600℃ at a rate of 3℃ / min under nitrogen atmosphere protection and carbonized for 3 hours. After the carbonized material cools down naturally, it is heated to 1400℃ at a rate of 3℃ / min under nitrogen atmosphere protection and carbonized for 3 hours to obtain hard carbon anode material.

[0029] The material obtained by testing Example 1 can be... Figure 1 As can be seen from the TEM characterization images, the material contains a large number of short-range ordered graphite-like microcrystals entangled and stacked in a microporous structure. This structure can provide a large amount of storage space for sodium ions. Figure 2 It can be known that the charging capacity is above 370mAh / g, through Figure 3 The pore size distribution shows that the internal structure of hard carbon is mainly composed of micropores smaller than 2 nm, and the structure can be controlled through a stepwise carbonization process.

[0030] Comparative Example 1

[0031] A. Using coconut shell carbon grown in Indonesia as raw material, the coconut shell carbon is pulverized to a median particle size of 10±0.5μm using an air jet mill. The pulverized material, water, hydrochloric acid, nitric acid and hydrofluoric acid are mixed in a ratio of 1:1.5:0.1:1.5:0.1 and stirred in a reaction vessel for 8 hours. After washing with deionized water until pH=6, the mixture is dried.

[0032] B. The obtained material is coated with phenolic resin in liquid phase. The mass ratio of phenolic resin to pretreated material is 8:100. Under nitrogen atmosphere protection, the temperature is raised to 1500℃ at a rate of 3℃ / min and carbonized for 3 hours to obtain hard carbon anode material.

[0033] Comparative Example 2

[0034] A. Using coconut shell carbon grown in Indonesia as raw material, the coconut shell carbon is pulverized to a median particle size of 10±0.5μm using an air jet mill. The pulverized material, water, hydrochloric acid, nitric acid and hydrofluoric acid are mixed in a ratio of 1:1.5:0.1:1.5:0.1 and stirred in a reaction vessel for 8 hours. After washing with deionized water until pH=6, the mixture is dried.

[0035] B. Transfer the obtained material to a carbonization furnace and heat it to 200°C at a rate of 5°C / min under nitrogen atmosphere protection. Hold the temperature for 3 hours to perform low-temperature pretreatment to remove excess moisture and volatiles, and obtain the material to be pretreated.

[0036] C. After the pretreated material cools down naturally, it is taken out and coated with phenolic resin in liquid phase. The mass ratio of phenolic resin to pretreated material is 8:100. After uniform dispersion, it is heated to 1500℃ at a rate of 3℃ / min for 3 hours under nitrogen atmosphere protection to obtain hard carbon anode material.

[0037] Comparative Example 3

[0038] A. Using coconut shell carbon grown in Indonesia as raw material, the coconut shell carbon is pulverized to a median particle size of 10±0.5μm using an air jet mill. The pulverized material, water, hydrochloric acid, nitric acid and hydrofluoric acid are mixed in a ratio of 1:1.5:0.1:1.5:0.1 and stirred in a reaction vessel for 8 hours. After washing with deionized water until pH=6, the mixture is dried.

[0039] B. The obtained material is coated with phenolic resin in the liquid phase. The mass ratio of phenolic resin to pretreated material is 8:100. After uniform dispersion, the material is heated to 500℃ at a rate of 3℃ / min under nitrogen atmosphere protection for 3 hours for low-temperature carbonization. After the carbonized material cools down naturally, it is heated to 1300℃ at a rate of 3℃ / min under nitrogen atmosphere protection for 3 hours for high-temperature carbonization to obtain hard carbon anode material.

[0040] Comparative Example 4

[0041] A. Using coconut shell carbon grown in Indonesia as raw material, the coconut shell carbon is pulverized to a median particle size of 10±0.5μm using an air jet mill. The pulverized material, water, hydrochloric acid, nitric acid and hydrofluoric acid are mixed in a ratio of 1:1.5:0.1:1.5:0.1 and stirred in a reaction vessel for 8 hours. After washing with deionized water until pH=6, the mixture is dried.

[0042] B. Transfer the obtained material to a carbonization furnace and heat it to 300°C at a rate of 5°C / min under nitrogen atmosphere protection. Hold the temperature for 3 hours to perform low-temperature pretreatment to remove excess moisture and volatiles, and obtain the material to be pretreated.

[0043] C. After the pretreated material cools down naturally, it is taken out and coated with phenolic resin in liquid phase. The mass ratio of phenolic resin to pretreated material is 8:100. After uniform dispersion, it is heated to 1100℃ at a rate of 3℃ / min under nitrogen atmosphere protection and carbonized for 3 hours. After the carbonized material cools down naturally, it is heated to 1600℃ at a rate of 3℃ / min under nitrogen atmosphere protection and carbonized for 3 hours to obtain hard carbon anode material.

[0044] Comparative Example 5

[0045] A. Using coconut shell carbon grown in Indonesia as raw material, the coconut shell carbon is pulverized to a median particle size of 10±0.5μm using an air jet mill. The pulverized material, water, hydrochloric acid, nitric acid and hydrofluoric acid are mixed in a ratio of 1:1.5:0.1:1.5:0.1 and stirred in a reaction vessel for 8 hours. After washing with deionized water until pH=6, the mixture is dried.

[0046] B. Transfer the obtained material to a carbonization furnace and heat it to 300°C at a rate of 5°C / min under nitrogen atmosphere protection. Hold the temperature for 3 hours to perform low-temperature pretreatment to remove excess moisture and volatiles, and obtain the material to be pretreated.

[0047] C. After the pretreated material cools down naturally, it is taken out and coated with phenolic resin in liquid phase. The mass ratio of phenolic resin to pretreated material is 8:100. After uniform dispersion, it is heated to 1200℃ at a rate of 3℃ / min under nitrogen atmosphere protection and carbonized for 3 hours. After the carbonized material cools down naturally, it is heated to 1600℃ at a rate of 3℃ / min under nitrogen atmosphere protection and carbonized for 3 hours to obtain hard carbon anode material.

[0048] Comparative Example 6

[0049] A. Using coconut shell carbon grown in Indonesia as raw material, the coconut shell carbon is pulverized to a median particle size of 10±0.5μm using an air jet mill. The pulverized material, water, hydrochloric acid, nitric acid and hydrofluoric acid are mixed in a ratio of 1:1.5:0.1:1.5:0.1 and stirred in a reaction vessel for 8 hours. After washing with deionized water until pH=6, the mixture is dried.

[0050] B. Transfer the obtained material to a carbonization furnace and heat it to 600°C at a rate of 5°C / min under nitrogen atmosphere protection. Hold the temperature for 3 hours to perform low-temperature pretreatment to remove excess moisture and volatiles, and obtain the material to be pretreated.

[0051] C. After the pretreated material cools down naturally, it is taken out and coated with phenolic resin in liquid phase. The mass ratio of phenolic resin to pretreated material is 8:100. After uniform dispersion, it is heated to 1300℃ at a rate of 3℃ / min under nitrogen atmosphere protection and carbonized for 3 hours. After the carbonized material cools down naturally, it is heated to 1600℃ at a rate of 3℃ / min under nitrogen atmosphere protection and carbonized for 3 hours to obtain hard carbon anode material.

[0052] The experimental data obtained from Comparative Examples 1-6 and Examples 1-2 are shown in the table below:

[0053]

[0054] As shown in the table above, by controlling the carbonization temperature of different embodiments and comparative examples, and by omitting the pretreatment steps or the low-temperature carbonization process accordingly, the effects of stepwise carbonization and non-stepwise carbonization on structural regulation can be observed. If high-temperature carbonization is performed directly, the specific surface area will not decrease, nor will the proportion of micropores increase. By changing the low-temperature carbonization temperature, if it exceeds the given range, a suitable micropore proportion cannot be obtained, and the specific surface area will not decrease, resulting in a low initial capacity efficiency.

[0055] The structure of hard carbon anode materials mainly consists of micropores, mesopores, and macropores. Constructing more micropores can significantly increase the sodium-ion storage space, thereby improving capacity and first-time efficiency. This invention focuses on using a stepwise carbonization process to regulate the pore structure of the material, increasing the proportion of micropores and decreasing the proportion of mesopores and macropores, while simultaneously reducing the specific surface area and improving the first-time efficiency. In the table above, different temperatures at different stages have varying effects on the structure. When stepwise carbonization is used, the specific surface area of ​​the material is significantly reduced. Furthermore, by controlling the low-temperature and high-temperature carbonization temperatures, more micropores can be constructed, achieving a suitable proportion of micropores, mesopores, and macropores. Additionally, the significant reduction in specific surface area is primarily due to the formation of closed micropores, which are undetectable.

[0056] In the description of this specification, specific features, structures, materials, or characteristics may be combined in any suitable manner in one or more embodiments or examples.

[0057] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A method for preparing a high-capacity hard carbon anode material for sodium-ion batteries, characterized in that, Includes the following steps: A. The biochar is pulverized, acid-washed, washed, filtered, and dried to obtain the first hard carbon precursor. The average pore size of the first hard carbon precursor is 25-40 nm, of which the total pore volume ratio of mesopores and macropores is 90-100%. B. Under a protective atmosphere, the first hard carbon precursor obtained in step A is pretreated to remove excess moisture, resulting in a pretreated material. The pretreatment temperature is 200-500℃, the heating rate is 0.5-5℃ / min, and the holding time is 1-5h; C. The pretreated material obtained in step B is coated with a coating agent to obtain a second hard carbon precursor, and then carbonized under a protective atmosphere to obtain a hard carbon anode material. The coating agent includes at least one selected from coal tar pitch, petroleum asphalt, natural asphalt, phenolic resin, and epoxy resin, and the mass ratio of the coating agent to the first hard carbon precursor is (1-10):

100. The carbonization process includes the following steps: first, pre-carbonization at a temperature of 500-1000℃ with a heating rate of 0.5-5℃ / min and a holding time of 1-5h; then, re-carbonization at a temperature of 1000-1600℃ with a heating rate of 0.5-5℃ / min and a holding time of 1-5h.

2. The preparation method according to claim 1, characterized in that, In step A, the pore volume ratio of the micropores is 0-10%, and the specific surface area is 100-500 m². 2 / g, with a particle size of 1-20μm.

3. The preparation method according to claim 1, characterized in that, In step A, the pulverization is performed by air jet milling, mechanical milling, or roller milling.

4. The preparation method according to claim 1, characterized in that, In step A, during the acid washing process, the pulverized biochar, water, hydrochloric acid, nitric acid and hydrofluoric acid are mixed in a mass ratio of 1:(1-10):(0.1-10):(0-15):(0-5).

5. The preparation method according to claim 1, characterized in that, In step C, the hard carbon anode material has an average pore size of 1-10 nm, a total pore volume ratio of 0-20% for mesopores and macropores, a pore volume ratio of 80-100% for micropores, and a specific surface area of ​​1-5 m². 2 / g, with a particle size of 1-10μm.

Citation Information

Patent Citations

  • Method for preparing hard carbon negative electrode material for sodium ion battery by adopting porous material

    CN114477130A

  • Coated carbon-based composite material as well as preparation method and application thereof

    CN116639678A